The Effects Of Inflation and Economic Growth Against the Provincial Minimum Wage in West Sumatra - Pratama, Bayu Akbar; Martilova, Novera (Transforma Jurnal Manajemen, 2023)
The aim of this research is to examine the extent of the influence of the variables of Inflation and Economic Growth on the Provincial Minimum Wage variable in West Sumatra within the time range of 1996-2021, with a partially and simultaneously. The method used in this study is quantitative. The data source used is secondary data obtained from the Central Statistics Agency (Badan Pusat Statistik or BPS) in West Sumatra. Multiple linear regression is used as the statistical analysis with SPSS version 26 as the tool for processing the multiple regression. The research results show that partially inflation has a significant influence on the Provincial Minimum Wage resulting in a significant value of 0.000 <0.05. Next, Economic Growth partially has a significant influence on the Provincial Minimum Wage with a significant value of 0.009 <0.05. Furthermore, Inflation and Economic Growth together, or simultaneously, have a significant influence on the Provincial Minimum Wage in West Sumatra with a significant value of 0.001 <0.05. The coefficient test results indicate that the variables under study resulted in an Adjusted R Square value of 0.218. This means that inflation and economic growth can explain 21.8% of the variations that occur in the dependent variable.